Sindbis virus replication, is insensitive to rapamycin and torin1, and suppresses Akt/mTOR pathway late during infection in HEK cells - Mohankumar, Vidyarani (2011)
Genetically engineered Sindbis viruses (SIN) are excellent oncolytic agents in preclinical models. Several human cancers have aberrant Akt signaling, and kinase inhibitors including rapamycin are currently tested in combination therapies with oncolytic viruses. Therefore, it was of interest to delineate possible cross-regulation between SIN replication and PI3K/Akt/mTOR signaling. Here, using HEK293T cells as host, we report the following key findings: a) robust SIN replication occurs in the presence of mTOR specific inhibitors, rapamycin and torin1 or Ly294002- a PI3K inhibitor, suggesting a lack of requirement for PI3K/Akt/mTOR signaling; b) suppression of phosphorylation of Akt, mTOR and its effectors S6, and 4E-BP1 occurs late during SIN infection: a viral function that may be beneficial in counteracting cellular drug resistance to kinase inhibitors; c) Ly294002 and SIN act additively to suppress PI3K/Akt/mTOR pathway with little effect on virus release; and d) SIN replication induces host translational shut off, phosphorylation of eIF2α and apoptosis. This first report on the potent inhibition of Akt/mTOR signaling by SIN replication, bolsters further studies on the development and evaluation of engineered SIN genotypes in vitro and in vivo for unique cytolytic functions.